2019
DOI: 10.1101/521633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent effects of the orexin-1 receptor antagonist SB-334867 on motivation for the fast acting opioid remifentanil

Abstract: For submission to the special issue: 'Orexin/hypocretin receptor antagonists for the treatment of addiction and related psychiatric disease: What are the steps from here?' (Eds. Aston-Jones and James). Abstract:The orexin (hypocretin) system is important for reward-seeking behavior. The orexin-1 receptor (Ox1R) antagonist SB334867 (SB) reduces seeking of food and drug reward under conditions of high motivation. There is some evidence that the effects of systemic SB on reward seeking persist beyond the pharmaco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Our laboratory and others have shown that systemic administration of the OxR1 antagonist SB attenuates drug seeking beyond the bioavailability of the compound [15,31]. Consistent with this, here we report that in rats with limited drug access, 30 mg/kg suvorexant increased fentanyl demand elasticity for ~24h.…”
Section: Persistent Effects Of Suvorexant On Fentanyl Demandsupporting
confidence: 89%
See 3 more Smart Citations
“…Our laboratory and others have shown that systemic administration of the OxR1 antagonist SB attenuates drug seeking beyond the bioavailability of the compound [15,31]. Consistent with this, here we report that in rats with limited drug access, 30 mg/kg suvorexant increased fentanyl demand elasticity for ~24h.…”
Section: Persistent Effects Of Suvorexant On Fentanyl Demandsupporting
confidence: 89%
“…Evidence generally supports a functional dichotomy for OxR1 vs OxR2 signaling, whereby OxR1 signaling preferentially mediates reward behaviors and OxR2 signaling modulates arousal and sleep [5]. Consistent with this, systemic treatment with selective OxR1 antagonists, including SB334867 (SB), reduce economic demand and cued reinstatement for all drugs of abuse tested, including the opioids fentanyl and remifentanil [14,15], but have limited effects on arousal and sleep [16][17][18]. In contrast, selective OxR2 antagonists promote sleep [18], and were reported to have limited effect on cocaine seeking behavior [19].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…lesions, pharmacological, chemogenetic and optogenetic) consistently and robustly implicate the VP in a variety of forms of relapse to seeking a variety of drugs of abuse, including alcohol, cocaine, heroin, remifentanil and natural reinforcers such as sucrose and food (e.g. Mahler et al, 2014; Mohammadkhani, James, Pantazis, & Aston‐Jones, 2020; Perry & McNally, 2013; Rogers, Ghee, & See, 2008; Smith & Berridge, 2005; Tang, McFarland, Cagle, & Kalivas, 2005). Indeed, the role of the VP in different forms of relapse to seeking a variety of drugs of abuse is so robust that the VP was proposed as key component of a “final common pathway” for relapse (Kalivas & Volkow, 2005) (Figure 1a).…”
Section: Ventral Pallidum (Vp) and Relapsementioning
confidence: 99%